Impact of Green Marketing on Sustainable Business Development in Nepal - Giri, Adarsha Raj (Nepalese Journal of Economics, 2025)
This study examined the impact of green marketing on sustainable business development in Nepal. Sustainable business development is the dependent variable. The selected independent variables are consumer behaviour, green marketing awareness, corporate social responsibility, government policies and regulations, and business innovations. The primary source of data is used to assess the opinion of respondents regarding consumer behaviour, green marketing awareness, corporate social responsibility, government policies and regulations, business innovations and sustainable business development. The study is based on primary data of 125 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of impact of green marketing on sustainable business development in Nepal. Sustainable business development is the dependent variable. The study showed a positive impact of consumer behaviour on sustainable business development. It indicates that positive consumer behaviour leads to create sustainable business development. Similarly, the study showed a positive impact of green marketing awareness on sustainable business development. It indicates that awareness about the green marketing leads to create sustainable business development. Likewise, the study showed a positive impact of corporate social responsibility on sustainable business development. It indicates that social and environmental impact of a company’s actions lead to create sustainable business development. Further, the study showed a positive impact of government policies and regulations on sustainable business development. It indicates that supportive government policies and regulations lead to create sustainable business development. In addition, the study showed a positive impact of business innovations on sustainable business development. It indicates that introducing new products, services, or processes leads to create sustainable business development.